6x-3(x+9)=9+2(3x-1)

Simple and best practice solution for 6x-3(x+9)=9+2(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3(x+9)=9+2(3x-1) equation:


Simplifying
6x + -3(x + 9) = 9 + 2(3x + -1)

Reorder the terms:
6x + -3(9 + x) = 9 + 2(3x + -1)
6x + (9 * -3 + x * -3) = 9 + 2(3x + -1)
6x + (-27 + -3x) = 9 + 2(3x + -1)

Reorder the terms:
-27 + 6x + -3x = 9 + 2(3x + -1)

Combine like terms: 6x + -3x = 3x
-27 + 3x = 9 + 2(3x + -1)

Reorder the terms:
-27 + 3x = 9 + 2(-1 + 3x)
-27 + 3x = 9 + (-1 * 2 + 3x * 2)
-27 + 3x = 9 + (-2 + 6x)

Combine like terms: 9 + -2 = 7
-27 + 3x = 7 + 6x

Solving
-27 + 3x = 7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-27 + 3x + -6x = 7 + 6x + -6x

Combine like terms: 3x + -6x = -3x
-27 + -3x = 7 + 6x + -6x

Combine like terms: 6x + -6x = 0
-27 + -3x = 7 + 0
-27 + -3x = 7

Add '27' to each side of the equation.
-27 + 27 + -3x = 7 + 27

Combine like terms: -27 + 27 = 0
0 + -3x = 7 + 27
-3x = 7 + 27

Combine like terms: 7 + 27 = 34
-3x = 34

Divide each side by '-3'.
x = -11.33333333

Simplifying
x = -11.33333333

See similar equations:

| 28=4x+4 | | 5[3x-5(7x+y)]= | | -36+2w=-8w+w | | 10r-2=28 | | 7x^2=-65x-18 | | 7m+3=24 | | 12-7x=50-14x | | (x-3)(x-4)=2 | | 5x+7=-53-10x | | 16=-2-z | | -5(3-4x)=6+20x-9 | | 16p^2-36= | | 5x+11=83-3x | | 3p+4q=52 | | x^2-8X-32=0 | | 2+3b=-4 | | 4(x+2)+10=6x-(x+9) | | -4(x+4)-3=-19 | | 5-8n=10 | | 4[7x-5(y-3)]= | | 6+4x=18+x | | 3c-6=5c+9 | | 5(x+2)-(x-2)=0 | | 8+1= | | 14-5n(3)=n | | 8x-14=2x+4 | | 6=2-4x | | 45-5x=4x+17 | | 11x-23=109 | | 8-8x=152-36x | | 3y-y+2y-5=7-y+5 | | 2(5m+4)-3(m-4)= |

Equations solver categories